Klasik De'Karas / Nur Zulaikha Ahmad Nazri, Allya Nur Zarifah Zamri and Athirah Amani Abd Razak - Ahmad Nazri, Nur Zulaikha; Zarifah Zamri, Allya Nur; Abd Razak, Athirah Amani (2023)
Klasik De'Karas is an initiatives from us to introduce Malay traditional food for customers. Nowadays, young generation does not care to preserve this food. We therefore combine our efforts to make sure that one of Malaysia's traditions does not vanish over time. Additionally, it might raise people's knowledge of Malaysia's SME sector, which might inspire more people to start their own enterprises. Along the process to start the business, we have been through many difficulty because we do not have any knowledge regarding running the business through online platform. Due to the fact that the majority of our customers spend more time on Facebook, it has been selected as the main platform to advertise our product. Furthermore, we sell our products across UiTM Puncak Alam in order to accomplish our goal of presenting kuih karas to the millennial generation in addition to serving as a nostalgic experience for the elderly. This show the reason why we choose to proceed with Malay traditional food as well as we try to keep continue to introduce this traditional food especially to Malaysian.